Deficiency of sorting nexin 10 prevents bone erosion in collagen-induced mouse arthritis through promoting NFATc1 degradation. Issue 6 (3rd July 2015) - Zhou, Chun; You, Yan; Shen, Weixing; Zhu, Yi-Zhun; Peng, Jing; Feng, Hao-Tian; Wang, Ying; Li, Dong; Shao, Wei-Wei; Li, Cui-Xian; Li, Wan-Zhen; Xu, Jiake; et al.
Abstract : Objective: Periarticular and subchondral bone erosion in rheumatoid arthritis caused by osteoclast differentiation and activation is a critical index for diagnosis, therapy and monitoring of the disease. Sorting nexin (SNX) 10, a member of the SNX family which functions in regulation of endosomal sorting, has been implicated to play an important clinical role in malignant osteopetrosis. Here we studied the roles and precise mechanisms of SNX10 in the bone destruction of collagen-induced arthritis (CIA) mice. Methods: The role of SNX10 in bone destruction was evaluated by a CIA mice model which was induced in male SNX10 −/− mice and wild type littermates. The mechanism was explored in osteoclasts induced by receptor activator of nuclear factor κB ligand from bone marrow mononuclear cells of wild type and SNX10 −/− mice. Results: SNX10 knockout prevented bone loss and joint destruction in CIA mice with reduced serum levels of TNF-α, interleukin 1β and anticollagen IgG 2α antibody. SNX10 deficiency did not block osteoclastogenesis, but significantly impaired osteoclast maturation and bone-resorption function by disturbing the formation of actin belt. The production of TRAP, CtsK and MMP9 in SNX10 −/− osteoclasts was significantly inhibited, and partially restored by SNX10 overexpression. We further demonstrated that the degradation of NFATc1 was accelerated in SNX10 −/− osteoclasts causing an inhibition of integrin β3-Src-PYK2 signalling. Conclusions: Our study discloses a crucial role and novel mechanism for SNX10 in osteoclast function, and provides evidence for SNX10 as a promising novel therapeutic target for suppression of immune inflammation and bone erosion in rheumatoid arthritis.